Concerns at the Level of European Union for the Protection of Critical Infrastructures - Iacob, Oana (Acta Universitatis Danubius. Juridica, 2024)
Critical infrastructures are particularly important for the smooth running and global evolution of the entire human society, at the level of all the states that make up the international community. For this reason, it is imperative that they are protected from the risks to which they are exposed and that all measures are taken to prevent and combat them as quickly as possible. Identifying the benefits that critical infrastructures bring to society and the best ways to protect them are some of the current concerns in the international context at the level of the European Union. By preventing and combating the major risks to which critical infrastructures are exposed, this study aims to ensure the smooth operation of the Union.